COGNIZING NON-TOXIC PRACTICES IN THE PRINT PROCESSES: A STUDY OF VARANASI - Kalyani, Ashwini R; Gupta, Peeyush Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Ecology, which is one of the essential practices of sustainable practice, is the talk of the town these days, and professionals from every domain are involved in such practices. This has also been observed in the print medium, where some artists and printmakers take prints using non-toxic materials. Since the ecological aspects of printing have been addressed in many research commentaries, most practitioners still use conventional printing methods and techniques, including materials (toxic), which derive from this research to investigate the significant reasons and construct the practicable framework for the non-practicing professionals and artists. It is well known that Varanasi is a city older than History; as Mark Twain said, thus on other cities can be a better option for conducting a comparative analysis of traditional and ecological print practices. After the argument, this paper reviews the advancements in printing processes used in Varanasi, focusing on toxic and non-toxic methods. It attempts to answer whether traditional printing practices are ecologically friendly. The first part of the paper briefly examines the spread of print media, the different trends and prevalent practices, and their impact on ecology in Varanasi. This part of the research and discussion is based on descriptive analysis. The second section of the paper focuses on current issues in ecology under three broad headings: theory and ecology, practice issues, and ecological effectiveness using discourse analysis to obtain responses from printmakers, and later it would be used to construct the research argument. An important thread running through the second part of the paper is related to discussions about the theory of ecology that is common in print practices and how these practices affect the various areas of ecology and their evaluation.